A retrospective screening and epidemiological study of oncological and other diseases in the oral and maxillofacial region at the University of Szeged, Department of Oral Medicine (1960-2014) - Sonkodi, I; Nagy, J; Novak, P; Braunitzer, G; Virag, K; Boda, K; Nagy, K (Fogorvosi szemle, 2016)
The Department of Oral Medicine at the University of Szeged was responsible for the stomato-oncological care of the population of three counties (with a population of 1,7 M at an average) in the period 1960-201 4. The present report summarizes the incidence of oral medicine diseases during this period. The overall number of new out-patients at the Department of Oral Surgery between 1960 and 2014 was 338,200. These patients were dental and oral surgical patients who presented spontaneously or were referred from the general practice, or stomato-oncological patients referred from general dental practices in-the three counties. Of the 338,200 new cases, 9,482 (2.8%) were benign tumors, 5438 (1.6%) premalignancies and 5,145 (1.5%) malignant tumors. This means a total of 20,065 tumor cases (5.9%) in the examined period, of which 10,579 (3.1 %) were premalignancies and malignancies. 14,446 patients presented with other diseases of the oral mucous membrane (5.8%, data available from 1974). Data on the number of stomato-oncological control patients in any given year are available from 1970 on. In the period 1970-2014, the total number of check-up patients was 117,268, this is the 76,97% of the departments overall number of patients. As for the tendencies, in the representative period of 1960-2004, the number of new benign tumors 15-fold, premalignancies 30-fold, and malignant tumors exhibited an 25-fold increase, while the number of other conditions affecting the oral mucosa showed a 14-fold increase.